Analysis of electromagnetic interaction between smooth and corrugated transmission lines by using a circuit model. Issue 2 (16th November 2022) - Wu, Chia Ho; Wu, Yu; Zhou, Guobing; Shen, Jianqi; Wang, Xiaolong; Wang, Zhuoyuan; Qian, Zhenyu; Shen, Linfang; Zhang, Hang; He, Fang; Chen, Gang; You, Yun
Abstract: It has been proved that a subwavelength periodic microstrip structure can be used to suppress crosstalk between two adjacent microstrip lines and such a microstrip structure can be widely used in the application of high‐speed circuit systems. To further increase the accuracy of the equivalent circuit model of the subwavelength periodic microstrip line (SPML), we focus our attention on a single unit cell with the periodic structure, which is divided into several sub‐regions, and the circuit parameters in each sub‐region are analysed for setting up a complete circuit model of the unit cells. Then the details of the interaction between each sub‐region and the electromagnetic field are clearly indicated. The S S ‐parameters of the circuit model accord well with full‐wave simulation results, showing a maximum deviation of 0.03973 dB for S 21 and 0.1211 dB for S 11 below 15 GHz. For the first time, we also study the frequency‐dependence of the mutual capacitance and the mutual inductance for analysing the coupling effect between an SPML and a conventional microstrip line (CML). The instantaneous impedance obtained by the full‐wave simulation of the SPML is consistent well with the experimental results. Abstract : For the first time, we also study the frequency‐dependence of the mutual capacitance and the mutual inductance for analysing the coupling effect between a subwavelength periodic microstrip line and a conventional microstrip line. The full‐wave method to calculate the S ‐parameters of the coupled circuit composed by the conventional microstrip line and the subwavelength periodic microstrip line is consistent with the circuit model.